A Decadence Baedeker: D'Annunzio's The Triumph of Death. Issue 1 (2nd January 2017) - Galbo, Joseph
Abstract: This article investigates how Gabriele D'Annunzio's The Triumph of Death brings together Nietzsche's ideas and Wagner's music and interweaves them with the motifs of literary Decadence and the author's own particular sexual politics. The novel is an experimental text striving to be a Gesemtkunstswerk, an integrated work that incorporates music, painting, poetry, regional folklore, and private thoughts about personal and national power. I discuss the novel's themes of violent sexuality and the anxiety of powerlessness and explore their implications for the fascist political aesthetics in which D'Annunzio played a pioneering role.